2020
DOI: 10.1073/pnas.2001263117
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated meta-perceptions predict intergroup hostility between American political partisans

Abstract: People’s actions toward a competitive outgroup can be motivated not only by their perceptions of the outgroup, but also by how they think the outgroup perceives the ingroup (i.e., meta-perceptions). Here, we examine the prevalence, accuracy, and consequences of meta-perceptions among American political partisans. Using a representative sample (n= 1,056) and a longitudinal convenience sample (n= 2,707), we find that Democrats and Republicans equally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
190
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(203 citation statements)
references
References 34 publications
9
190
4
Order By: Relevance
“…This was followed by questions about who they believe to have won the election and opinions about fraud, after informing them that that "news organizations (e.g., Fox News, NBC, ABC, the Associated Press) have called the election in favor of Joe Biden", they were asked the questions about Trump conceding/losing court challenges (Figure 3 -see supplement). Next, participants completed three partisan spite (Moore-Berg et al, 2020) and four partisan violence (Kalmoe & Mason, 2019) questions in a random order. As noted in Figure 5, the questions used "Democrat" and "Republican" depending on which was the in-party and out-party for the individual (and, hence, only those who indicated an affiliation with either party were administered the questions).…”
Section: Methodsmentioning
confidence: 99%
“…This was followed by questions about who they believe to have won the election and opinions about fraud, after informing them that that "news organizations (e.g., Fox News, NBC, ABC, the Associated Press) have called the election in favor of Joe Biden", they were asked the questions about Trump conceding/losing court challenges (Figure 3 -see supplement). Next, participants completed three partisan spite (Moore-Berg et al, 2020) and four partisan violence (Kalmoe & Mason, 2019) questions in a random order. As noted in Figure 5, the questions used "Democrat" and "Republican" depending on which was the in-party and out-party for the individual (and, hence, only those who indicated an affiliation with either party were administered the questions).…”
Section: Methodsmentioning
confidence: 99%
“…While we may have strong stereotypes about both the other party and our own, our beliefs about "us" are at least still modulated by the details of the local context. Examining how partisan extremity affects the accuracy of ingroup meta-perception is a fruitful avenue of future research, as recent work suggests ideological extremity exacerbates the inaccuracy of outgroup meta-perception among Democrats and Republicans (Moore-Berg, Ankori-Karlinsky, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Democrats and Republicans with the most extreme ideological attitudes were the most likely to overestimate the levels of prejudice and dehumanization their respective out-party held toward them. These inaccurate meta-perceptions were, in turn, uniquely associated with a willingness to violate democratic norms in favor of ingroup loyalty (Moore-Berg, Ankori-Karlinsky, et al, 2020). Inaccurate meta-perceptions also play a role outside the domain of politics.…”
Section: How Inaccuracy In First Vs Second-order Beliefs Lead To Actmentioning
confidence: 99%
“…Similarly, Kteily & Bruneau (2017a), found among members of Latinx and Muslim minorities in the United States that feelings of being dehumanized by Americans predicted reciprocal feelings of dehumanization, which mediated increased support for violent, versus nonviolent, collective action. Most recently, meta-dehumanization expressed by American Democrats and Republicans has been shown to predict support for intergroup hostility, again mediated through higher levels of outgroup dehumanization (Moore-Berg et al, 2020). However, given that the negativity of meta-perceptions tends to be exaggerated (Frey & Tropp, 2006;Moore-Berg et al, 2020), providing individuals with the opportunity to engage directly with the outgroup and hear their perspectives may effectively diminish intergroup hostility by correcting overly pessimistic meta-perceptions.…”
Section: Contact and Meta-perceptionsmentioning
confidence: 99%
“…Most recently, meta-dehumanization expressed by American Democrats and Republicans has been shown to predict support for intergroup hostility, again mediated through higher levels of outgroup dehumanization (Moore-Berg et al, 2020). However, given that the negativity of meta-perceptions tends to be exaggerated (Frey & Tropp, 2006;Moore-Berg et al, 2020), providing individuals with the opportunity to engage directly with the outgroup and hear their perspectives may effectively diminish intergroup hostility by correcting overly pessimistic meta-perceptions. For example, Kteily et al (2016) demonstrated that Americans harbor strong negative meta-perceptions with respect to Muslims-believing that Muslims both dislike and dehumanize Americanswhich is at odds with Pew surveys collected over the last decade indicating that Muslims across the world have positive views of Americans (Diamant, 2017).…”
Section: Contact and Meta-perceptionsmentioning
confidence: 99%